PERAN GURU BIMBINGAN DAN KONSELING DALAM MENINGKATKAN HUBUNGAN SEBAYA MENGENAI KEDEWASAAN DI SMK MUHAMMADIYAH 13 SIBOLGA - Asmaryadi, Asmaryadi (Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2017)
In this research paper the author wishes to see the real picture of the efforts of teacher guidance and counseling in improving peer relationships maturity of students of SMK Muhammadiyah 13 Sibolga 2013-2014 school year. This research background by the level of development of peer relationships that are not in accordance with the development age because there are many students who are addressing the problems faced by the negative action as they fled into the things that are negative as excessive mischief. all the result of a lack of maturity in students' peer relationships. There are two variables in this study, namely x and, y first variable is aimed to determine whether there was an attempt teacher guidance and counseling (x) relationship maturity in peer students of SMK Muhammadiyah 13 Sibolga (y). objects were students and teachers of SMK Muhammadiyah BK 13 Sibolga result data can conduct interviews and observations in the field observation on the research object student teachers and peers. The method used is descriptive qualitative research methods in qualitative research does not use the term population but as word (Spradley, in Sugioyono, 2012: 297) through three stages, namely the situation, taxonomy, area. Because the population of generalization that occurs over the object and subject that has certain qualities that set by the researcher to learn kemudin be deduced. of research gets results category "Good" data analysis showed that the teachers bimbinganan counseling efforts in improving peer relationships maturity reached the expected value by BK teachers in this study